The Holy Quran and its Sciences in the Digital Environment - Study of contents and interactions - - Yssaad, Zahia El-Ssaid; Toumi, Fadhila (Journal of Humanities & Social Sciences, 2020)
This research aimed to examine the extent of the use of social networks to serve the Holy Qur’an and its sciences, publish its contents among subscribers, exchange and benefit from them, and benefit from them, after closely examining the most important topics and Quranic contents on the Twitter and Facebook pages and the extent of the interaction of Arab users with those contents within the framework Religious media seeking to exploit the available platforms in various methods and means using the descriptive method and the content analysis tool, Therefore, it became clear to us that there is a large presence of the Quranic text and the sciences emanating from it on social networking sites through hundreds of active pages managed by interested people who carried on their shoulders the electronic invitation. Among the rest of the content is that these publications were by users, so we hope that religious institutions in the Arab world will strive to intensify their publications and use innovative methods to promote religious content and enable it to address all calls to mistake young people in the digital space.
Keywords: Quranic sciences; social networking sites; interactivity; content; use